MODEL DEBAT TERSTRUKTUR POINT-COUNTERPOINT SEBAGAI BENTUK DISKUSI PADA MATA PELAJARAN AKIDAH AKHLAK BAGI SISWA MADRASAH TSANAWIYAH NEGERI 2 KOTA JAMBI - Wati, Laras; Fahri, Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low student participation and lack of direction in discussion activities in the learning of Akidah Akhlak at Madrasah Tsanawiyah Negeri 2 Jambi City. This condition causes learning interactions to not take place optimally and learning objectives that emphasize the development of critical thinking skills and the formation of morals have not been achieved optimally. This study aims to describe the planning, implementation, and implications of the implementation of the Point-Counterpoint Structured Debate Model as a form of discussion in learning Akidah Akhlak. The study used a descriptive qualitative approach with the research subjects of Akidah Akhlak teachers and eighth grade students. Data were collected through observation, interviews, and documentation, then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that the planning of the model was carried out through the preparation of learning objectives, selection of controversial materials, formation of point and counterpoint groups, and the preparation of clear debate rules. The implementation of the model took place systematically with the guidance of the teacher as a facilitator so that the discussion ran orderly and directed. The implementation of this model has positive implications for increasing student engagement, courage to express opinions, critical thinking skills, the ability to construct arguments, and respect for differing opinions in accordance with Islamic moral values. Thus, the Point-Counterpoint Structured Debate Model can be an effective learning alternative for creating conducive discussions and improving the quality of Aqidah Akhlak (Islamic Faith) learning